2011
DOI: 10.1111/j.1748-5967.2011.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy and non‐target effects of temephos granules against Culex pipiens (Diptera: Culicidae) and microorganisms in septic tanks, Republic of Korea

Abstract: A granular formulation of 1.0% temephos (temephos G) was tested for its efficacy in mosquito larval control, residual effects and effects on non‐target microorganisms. Culex pipiens complex in septic tanks in Yangsan, Republic of Korea were used for this study. Microorganisms in the same septic tanks were used for study of non‐target organisms. After the application of temephos G at the rates of 2.0 and 5.0 mg/L to selected septic tanks, mortalities were recorded for 50 days. The effect of temephos G on non‐ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…It has been suggested that the chemical characteristics of septic tank water, such as DO and turbidity, did not seem to affect the abundance or the control of Cx. pipiens larvae in septic tanks (no description of septic tank systems) treated with temephos (Kang et al 2011). Temephos 5% granule applied at 10 ppm active ingredient (AI) to scrap tires was reported to provide 100% mortality of Aedes triseriatus (Say) larvae for 14 mo with a drop to 21% mortality after 21 mo (Beehler et al 1991).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that the chemical characteristics of septic tank water, such as DO and turbidity, did not seem to affect the abundance or the control of Cx. pipiens larvae in septic tanks (no description of septic tank systems) treated with temephos (Kang et al 2011). Temephos 5% granule applied at 10 ppm active ingredient (AI) to scrap tires was reported to provide 100% mortality of Aedes triseriatus (Say) larvae for 14 mo with a drop to 21% mortality after 21 mo (Beehler et al 1991).…”
Section: Discussionmentioning
confidence: 98%
“…However, application rate of 2 ppm (AI) of temephos 1% water soluble granule to EF of septic tanks resulted in 100, 68, and 43% mortality of Cx. pipiens larvae at 8, 29, and 50 DAT, respectively (Kang et al 2011), suggesting a need for repeated treatments for the effective mosquito control.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, several chemical insecticides that have been traditionally applied for mosquito control are banned or restricted in developed countries 3 . For example, one of the most commonly used larvicides worldwide is the organophosphate temephos, which can effectively control mosquito larvae by inhibiting cholinesterase enzyme activity in the acetylcholine receptors of the insect nervous system 8 . However, temephos use was phased out in the EU ~ 10 years ago leaving a gap in mosquito control 9,10 …”
Section: Introductionmentioning
confidence: 99%